Is Previous Periacetabular Osteotomy Associated with Pregnancy, Delivery, and Peripartum Complications?. Issue 1 (January 2020) - Bartosiak, Kimberly; Stockburger, Chris; Stockburger, Jennifer; Putnam, Sara; Conner, Shayna; Clohisy, John
Abstract: Background: Surgical candidates for periacetabular osteotomy are commonly women of reproductive age with symptomatic acetabular dysplasia. However, little is known about how this surgical intervention contributes to the decision to become pregnant, obstetrical counseling regarding delivery, mode of delivery, or pregnancy-related complications. Questions/purposes: (1) Does a history of periacetabular osteotomy affect a patient's decision to become pregnant or does it affect obstetrical counseling regarding the safety of pregnancy and childbirth? (2) Is history of periacetabular osteotomy associated with in an increased risk of undergoing cesarean section compared with the national average? (3) Is a history of periacetabular osteotomy associated with increased complications, decreased infant birth weight, preterm delivery? Methods: In conjunction with obstetrician colleagues, we created a survey to investigate patient attitudes toward pregnancy, mode of delivery, pregnancy-related complications, and obstetrical counseling among female patients who previously underwent periacetabular osteotomy. A retrospective cohort of reproductive-age women who underwent periacetabular osteotomy between 2008 and 2015 completed a mailed survey or telephone interview. All 96 patients who were contacted were asked if the history of periacetabular osteotomy affected their decision to become pregnant. Our cohort included 31 patients who had undergone periacetabular osteotomy and had a subsequent pregnancy and delivery with a total of 38 pregnancies resulting in 41 births. A binomial test was used to determine if the rates of cesarean section, low birth weight, or preterm delivery were different from the documented US national average as published by the National Vital Statistics Report and CDC. Results: One patient of 31 felt her periacetabular osteotomy negatively affected the appearance of her child; this surgical history affected 6.5% of patients (2 of 31) positively. Fifty-five percent (17 of 31) patients reported that their obstetrician expressed concern that their history of periacetabular osteotomy could affect their ability to carry to term or deliver vaginally. With a history of periacetabular osteotomy, 53% of deliveries (20 of 38) underwent cesarean section. This is higher than the national average of 32% (odds ratio 0.424 [95% confidence interval 0.214 to 0.837]; p = 0.006). Only one patient with a periacetabular osteotomy suffered a pregnancy-related complication. In singleton pregnancy after periacetabular osteotomy the preterm delivery rate was 14% (5 of 35) and the percentage of low-birth-weight infants was 2.9% (1 of 35). These percentages are not different from US data published by the National Vital Statistics Report, which reports an 8% preterm delivery rate (OR 0.523 [95% CI 0.154 to 1.772]; p = 0.1723) and 6.4% low birth weight (OR 2.34 [95% CI 0.607 to 9.025]; p = 0.3878) in singleton pregnancies. Conclusions: In this small survey study, we found no differences in terms of complications, preterm delivery or low birth weight infants between patients who had a history of periacetabular osteotomy and normative national data regarding complications of pregnancy and delivery. However, we did note that patients with a history of periacetabular osteotomy were more likely to deliver future children by cesarean section, which could be attributable to obstetrician preference as most obstetricians in another small survey study have expressed concern about patients with a history of periacetabular osteotomy. Future studies should aim to increase the knowledge of the association of periacetabular osteotomy and delivery method, specifically with transition to cesarean for failure to progress during labor. Future consideration of using the Academic Network of Conservational Hip Outcomes Research repository to develop National Surgical Quality Improvement Program data may help to elucidate this relationship more clearly and help guide appropriate indications for scheduled cesarean sections in the setting of prior pelvic osteotomy. Level of Evidence: Level IV, therapeutic study.